2001
DOI: 10.1046/j.1440-1746.2001.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter prospective analysis of newly diagnosed hepatocellular carcinoma with respect to the percentage of Lens culinaris agglutinin‐reactive α‐fetoprotein1

Abstract: Serum AFP concentration does not reveal a malignancy of HCC, however, the AFP-L3-positive HCC has biologically malignant characteristics, especially portal vein invasion and lower tumor classification, and is an advanced tumor regardless of small tumor size and lower serum AFP concentration. As AFP-L3 shows the tumor characteristics, its presence should be an important factor in the determination of therapy and prognosis of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 11 publications
2
91
1
Order By: Relevance
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012). Other research studies (Riener et al, 2009;Hu et al, 2010) observed that GP-73 levels were significantly higher in patients with hepatitis C-derived HCC and a high tumor grade.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012). Other research studies (Riener et al, 2009;Hu et al, 2010) observed that GP-73 levels were significantly higher in patients with hepatitis C-derived HCC and a high tumor grade.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the level of AFP is elevated in patients with both HCC and chronic liver disease; thus, there is wide overlapping between the two groups [144,145]. Most studies adopt a cutoff value of 20 ng/mL for AFP, with a sensitivity ranging from 49 to 71% and specificity from 49 to 86% in HCCs smaller than 5 cm [146][147][148][149][150][151][152][153][154]. Limitations in the sensitivity and specificity of AFP in surveillance of high-risk populations have led to the use of US as an additional method for the detection of HCC [142,[155][156][157].…”
Section: What Modality Should Be Used?mentioning
confidence: 99%